(untitled) (Bangladesh Critical Care Journal, 2023)
Mesenteric panniculitis or sclerosing panniculitis is a chronic nonspecific inflammation of mesentery adipose tissue of small intestine and colon. It can also rarely involve retroperitoneal, pelvic and peripancreatic fat. No specific etiology has been found behind this rare disease. It is most commonly associated with abdominal surgery, autoimmune disease and malignancy. Here we present a case of a middle-aged man with history of abdominal surgery and he was presented to us with dengue fever. His hospital course was complicated with sudden, severe abdominal pain with clinical features of subacute intestinal obstruction, and mesenteric panniculitis was diagnosed during further evaluation. It was a great challenge for us not only to diagnose such a disease of rare spectrum, but also to manage this patient who was already suffering from another agonizing disease, dengue fever Bangladesh Crit Care J March 2023; 11 (1): 61-64